Development of ViBot to Train Digital Literacy of 10th Grade High School Student - Savitri, Nandita Eka; Susantini, Endang (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2025)
The world is transitioning toward Society 5.0, characterized by increasing globalization and advancements in digital technology, leading to substantial societal transformations, including the rise of Artificial Intelligence (AI), the Internet of Things, Big Data, and robots. Education may capitalize on this by utilizing ICT-based learning media accessible via diverse electronic device. Furthermore, it possesses the capacity to improve digital literacy competencies. Telegram is one of the available technologies. A survey conducted among 20 students revealed that 70% utilize the Telegram application, while its use for academic is infrequent. This project aims to create a valid, practical, and effective Telegram bot for acquiring knowledge about viruses. This study employs the 4D method (Define, Design, Develop, and Disseminate). Data were gathered utilizing validation procedures, Fry readability assessments, questionnaires, and examinations. The research trial was conducted on 20 students from Labschool Unesa 1 High School. We examined the gathered data employing descriptive-quantitative methodologies. The research findings indicate that ViBot possesses a high validity score of 3.87, rendering it appropriate for educational purposes; it is regarded as practical according to the readability assessment, which yielded a level 10 and a student response rate of 97.5%; ViBot is classified as highly effective based in the comprehensiveness of digital literacy indicators, achieving a percentage of 83.75%, which falls within the very good category. Consequently, we can ascertain that ViBot is valid, practical, and effective for imparting digital literacy in the 10th grade.